حالات الحكم بالابعاد القضائي في التشريع الإماراتي: دراسة مقارنة - الخيلي، جمعة محمد; العاني، محمد شلال; النوايسة، عبدالله (جامعة الشارقة, 2022)
تبين لنا من دراسة موضوع حالات الإبعاد القضائي، بأنه موضوع يحظى بأهمية قانونية في مجال قانون العقوبات الاتحادي والتشريعات الجنائية الخاصة في دولة الإمارات العربية المتحدة، باعتباره جزاء جنائيا قاسيا على الشخص الأجنبي الذي يدان بارتكاب جريمة معينة على أراضي دولة الإمارات التي يقيم فيها. وعليه فإن محل جزاء الإبعاد القضائي يكون الشخص الأجنبي الذي يرتكب إحدى الجرائم المنصوص عليها في كافة القوانين الجزائية الإماراتية. وأن القضاء الإماراتي هو الذي حدد ويقدر جسامة الخطورة الإجرامية التي يترتب عليها حكم تدبير الإبعاد. وقد فرق المشرع الاتحادي بين نوعين من الإبعاد القضائي، وهما: الإبعاد القضائي الوجوبي، والإبعاد القضائي الجوازي. ففي الحالة الأولى حدد جملة من حالات الحكم بتدبير الإبعاد، وأوجب على المحكمة أن تأمر بإبعاد الأجنبي المحكوم عليه بعقوبة مقيدة للحرية في جميع الجنايات، ومنها الجنايات الواقعة على العرض والجرائم الماسة بأمن الدولة وجريمة الإضراب والجرائم الماسة بالعقائد والشعائر الدينية، هذا بالإضافة إلى بعض الحالات الأخرى الواردة في تشريعات جزائية خاصة نصت عليها قوانين عديدة، كقانون دخول وإقامة الأجانب وقانون مكافحة المواد المخدرة والمؤثرات العقلية وقانون جرائم مكافحة تمويل الإرهاب والاتجار بالبشر وقانون أحداث الجانحين والمشردين. أما في الإبعاد الجوازي؛ فإن للمحكمة أن تفاضل أو تختار عند إدانة الأجنبي بعقوبة مقيدة للحرية بين إبعاده أو عدم إبعاده، وذلك بعد التحقق من مدى خطورته الإجرامية على المجتمع. وقد تعرضنا للإبعاد القضائي بالقدر الذي يتجاوب مع الدراسة النظرية واستقراء الآراء الفقهية المقارنة المؤيدة والمعارضة للإبعاد. ودعمنا هذه الدراسة بتطبيقات قضائية من أحكام المحاكم المقارنة والإماراتية وغيرها من الشواهد والتطبيقات القانونية والفقهية المقارنة. وظهر لنا من هذه الدراسة بأن الإبعاد القضائي تدبير جنائي مقيد للحرية السالبة في التشريع الإماراتي، وكيف أن الخطورة الإجرامية شرط أساسي للحكم بتدبير الإبعاد وفقا للتشريع الجنائي الإماراتي؛ لذا طلبنا من هذا الأخير التدخل لتحديد مدة إبعاد الأجنبي، بما يلائم نوع الجريمة التي يرتكبها وبحسب خطورته على المجتمع. It became clear from the study of the issue of judicial deportation cases that it is a subject of legal importance in the field of the Federal Penal Code and the special criminal legislation in the United Arab Emirates, as it is a severe criminal penalty for a foreign person who is convicted of committing a specific crime on the territory of the UAE country in which he resides. Accordingly, the subject of judicial deportation arises when the foreign person who commits one of the crimes stipulated in all UAE criminal laws. Actually, it is the UAE judiciary that has determined and evaluated the gravity of the criminal risk involved in the ruling on deportation. The federal legislator distinguished between two types of judicial deportation, namely: mandatory judicial deportation and permissible judicial deportation. In the first case, the Emirati legislator identified a number of cases of ruling on the arrangement of deportation and obligated the court to order the deportation of the foreigner who was sentenced to a freedom restricting verdict in all crimes. These include crimes on display, crimes affecting state security, the crime of strike, crimes against religious beliefs and rituals. To this are added some other cases mentioned in special penal legislation stipulated by many laws, such as the law on entry and residence of aliens, the law against narcotic drugs and psychotropic substances, along with the criminal law against combating the financing of terrorism and human trafficking and the law for juvenile offenders and the homeless. As for passport expulsion, the court may choose or not choose, upon conviction of a foreigner, a penalty restricting freedom between his or her expulsion, after verifying the extent of the criminal danger to society. We have dealt with judicial expulsion to the extent that responds to the theoretical study and extrapolation of comparative jurisprudence opinions supporting and opposing deportation. We supported this study with judicial applications from the rulings of comparative and Emirati courts and other evidence as well as comparative legal and jurisprudential applications. We conclude from this study that judicial deportation is a criminal measure that restricts negative freedom in the legislation of the UAE criminal legislation, and how criminal risk is a prerequisite for the ruling deportation according to Emirati Legislator. We therefore request the latter to intervene to determine the period of deportation of the foreigner, in accordance with the type of crime he has committed and its threat to society.
Keywords: التشريعات الجنائية -- القانون الإماراتي -- السلطة القضائية -- الأبعاد القضائي -- السلطة التنفيذية